Tireless creation and getting to know the Creator: On the occasion of the jubilee of Professor Martina Orožen and the 150th anniversary of Graz Slavic Studies - Karničar, Ludvik (Slavia Centralis, 2021)
The University of Graz, especially the departments of Slavic and Slovene Studies, was an important educational and research center for Slovenes, and the city of Graz was one of the birthplaces of the Slovene national culture in the 19th century. The scientific path of Professor Orožen, who is celebrating her 90th birthday this year, was strongly intertwined with Graz Slavic studies.
Keywords: Slavic Studies; Slovene Studies; Graz; Janez Nepomuk Primic; Gregor Krek; Martina Orožen